COMPARATIVE LEGAL ANALYSIS OF THE LEGAL REGULATION OF THE MEDIATION INSTITUTE IN EU COUNTRIES AND IN UKRAINE. - Machuska, Iryna; Nedilchenko, Svitlana; Сhyryk Olena (SWorldJournal, 2025)
The article examines the institution of mediation as an alternative form of dispute and conflict resolution in the EU countries and in Ukraine. The article notes the importance of Directive 2008/52/EC of the European Parliament and of the Council on certa